An evaluation of the effect of plastic bag fee on consumer behavior: Case of Turkey - DUMLUDAĞ, DEVRİM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The purpose of this study is to examine the impact of the plastic bag fee (that was implemented in Turkey recently) on the consumer behavior. For this purpose, a face-to-face consumer survey with 821 respondents was conducted in Istanbul. A paired sample t-test was carried out in order to compare consumers' average frequency of using plastic bags, bringing their own bags for shopping, using plastic bags obtained in shopping for domestic waste and purchasing bin bags for domestic waste before/after the implementation of the policy of charging for plastic bags. Two different multiple regression analyses were carried out to determine which factors affect the change in plastic bag demand by the consumers for when the plastic bags were free of charge and for when they were paid. The results suggest that there has been a statistically significant change in consumers' behaviors towards using plastic bags in shopping and the means of keeping domestic waste. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Environment; Sustainable development; Single-use plastic bag; Plastic bag charge; Consumer behavior; Behavior change intervention; ATTITUDES; LESSONS; TAX